Capital Longevity and Economic Growth - Bhattacharyya, S. K. (Review of Economic Studies, 1965)
Journal Article Capital Longevity and Economic Growth Get access S. K. Bhattacharyya S. K. Bhattacharyya London School of Economics and Calcutta University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 1, January 1965, Pages 39–46, https://doi.org/10.2307/2296329 Published: 01 January 1965